Atomic commitment and resilience in grid database systems. (17th May 2005) - Goel, Sushant; Sharda, Hema; Taniar, David
Atomic Commitment Protocol (ACP) is an important part of any distributed transaction. ACPs have been proposed for homogeneous and heterogeneous distributed database management systems (DBMS). ACPs designed for these DBMS do not meet the requirement of Grid databases. Homogeneous DBMS are synchronous and tightly coupled while heterogeneous DBMS, like multi-database systems require a top layer of multi-database management system to manage distributed transactions. These ACPs either become too restrictive or need some changes in participating DBMS, which may not be acceptable in Grid Environment. In this paper, we identify requirements for Grid database systems and then propose an ACP for grid databases, Grid-Atomic Commitment Protocol (Grid-ACP). We then extend Grid-ACP to handle failure of database sites.